Teacher Facilitator Meningkatkan Kemampuan Penilaian Autentik pada Guru SDN 36 Gedong Tataan Kecamatan Gedong Tataan Kabupaten Pesawaran Tahun 2019 - Dewi, Siaga (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
This School Action Research (PTS) started from the background of the need to improve the ability of teachers to manage assessments in elementary schools as a response to the weak quality of student assessment. The research was conducted at SDN 36 Gedong Tataan with the aim of looking at the improvement of cognitive abilities and psychomotor abilities regarding authentic assessments of teachers at SDN 36 Gedong Tataan. This study uses a reflective action research design carried out in 3 cycles. The research subjects were teachers of SDN 36 Gedong Tataan, totaling 7 people. The results of data analysis for each cycle indicate that the Teacher Facilitator model can improve cognitive abilities and psychomotor abilities regarding authentic assessments of teachers at SDN 36 Gedong Tataan.